2002
DOI: 10.1007/s00421-002-0618-0
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cold ambient temperature on palmar sweating response to vibration stress

Abstract: We investigated the effect of cold ambient temperature on the palmar sweating response to vibration stress. Ten healthy, male subjects were exposed to eight ambient temperatures (5, 7, 10, 14, 18, 22, 24 and 28 degrees C). At each ambient temperature, each subject gripped the handle of a vibration generator with his left hand with a grasp strength of 49 N. This hand was then exposed to a 125-Hz sinusoidal vibration with an acceleration of 50 m/s(2) (rms) for 3 min at each ambient temperature. Palmar sweating a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…In earlier experimental studies, we observed a marked palmar sweating response during such forms of physical stress as exposure to cold ambient temperatures and hand-arm vibration (4,5). Exposure to noise was also observed to induce a palmar sweating response (6).…”
mentioning
confidence: 77%